A comparison of left ventricular function in patients undergoing beating heart bypass surgery using mixed versus pure venous conduits - Chaudhary, Tarun; Nautiyal, Hemant Kumar; Nahak, Aratatran; Sahu, Shantanu (International Surgery Journal, 2017)
Background: The pathophysiology of coronary artery disease was established in 1876 by Adam Hammer when he postulated that angina is caused by interruption of coronary blood supply and that myocardial infarction occurred after the occlusion of at least one coronary artery. Aims of the study were to compare the left ventricular function in patients who have undergone beating heart bypass surgery using mixed (internal mammary artery and venous conduits) versus pure Venous conduits, and to compare the incidence of postoperative complications. Methods: It was an observational, analytical study. All patients admitted with triple vessel disease requiring CABG (n=50), with ejection fraction >30%, were subjected to either left internal mammary artery and venous conduits (group A, n=25) or only venous conduits (group B, n=25). Patient who had undergone prior surgical myocardial revascularization, preexisting valvular disease, any evidence of raised pulmonary arterial pressure more than 40/15 mmHg, operated using cardiopulmonary bypass machine, pre-operative use of Intra-Aortic Balloon Pump, any history of neurological dysfunction/Transient ischemic attack, left atrium size more than 5.5 cm were excluded from the study Results: Improvement in left ventricular function after coronary artery bypass grafting was objectively demonstrated in both the groups. There was a statistically significant increase in mean LVEF in group B (56.16±4.13) compared to group A (51.96±5.30) at 3 months of follow up (p=0.009). The most common complication in both the groups were atrial fibrillation group A=36% (n=9), group= B 16 % (n=4), renal failure group A=12% and group B=8% and sternal wound infection. The post-operative bleeding (Drain output) in first 24 hours was similar in both the groups, 295.56 ml in group A and 265.20ml in group B (p=) with similar hospital stay (group A=9days, group B=8.5days). Conclusions: Patients with venous conduits have better postoperative LVEF as compared to Mixed conduit with similar rate of post-operative complications.